2007
DOI: 10.1186/1475-2840-6-8
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: As a part of a larger study investigating the effects of α-tocopherol on gene expression in type 2 diabetics we observed a pro-oxidant effect of α-tocopherol which we believe may be useful in interpreting outcomes of large intervention trials of α-tocopherol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…All studies involved patients diagnosed with T2DM (n = 1430) and were conducted mainly in Iran (n = 9 trials) [ 25 , 32 – 34 , 38 , 41 , 43 , 44 , 48 , 51 ]; followed by the United Kingdom (n = 4) [ 42 , 49 , 52 , 53 ] and the United States of America (n = 3) [ 28 , 29 , 47 ]. Evaluated treatments comprised: vitamin B (n = 1 study) [ 25 ], vitamin C (n = 10) [ 26 , 27 , 29 , 34 , 37 , 38 , 40 42 , 50 ]; vitamin D (n = 7) [ 30 , 35 , 43 , 44 , 48 , 49 , 53 , 55 ]; vitamin E (n = 12) [ 28 , 32 – 34 , 36 , 39 , 45 47 , 51 , 52 , 54 ], and a mixture of vitamins B, C and E (n = 1) [ 31 ]. In four of these trials (13.3%), vitamins were delivered by food fortification (oil or yogurt) [ 32 , 44 , 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies involved patients diagnosed with T2DM (n = 1430) and were conducted mainly in Iran (n = 9 trials) [ 25 , 32 – 34 , 38 , 41 , 43 , 44 , 48 , 51 ]; followed by the United Kingdom (n = 4) [ 42 , 49 , 52 , 53 ] and the United States of America (n = 3) [ 28 , 29 , 47 ]. Evaluated treatments comprised: vitamin B (n = 1 study) [ 25 ], vitamin C (n = 10) [ 26 , 27 , 29 , 34 , 37 , 38 , 40 42 , 50 ]; vitamin D (n = 7) [ 30 , 35 , 43 , 44 , 48 , 49 , 53 , 55 ]; vitamin E (n = 12) [ 28 , 32 – 34 , 36 , 39 , 45 47 , 51 , 52 , 54 ], and a mixture of vitamins B, C and E (n = 1) [ 31 ]. In four of these trials (13.3%), vitamins were delivered by food fortification (oil or yogurt) [ 32 , 44 , 48 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analyses of the glycemic control parameters (17 included trials obtained from 18 articles) are shown in Figs. 3 , 4 [ 28 30 , 33 , 35 39 , 43 , 44 , 46 49 , 52 , 53 , 55 ]. No statistical differences were observed in subgroup analyses comparing vitamins C or D with placebo.…”
Section: Resultsmentioning
confidence: 99%
“…STZ induced diabetes animals produced systolic and diastolic dysfunction [ 25 ]. Diabetic control showed reduced systolic blood pressure, diastolic blood pressure, end diastolic blood pressure, and mean arterial blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Although high plasma vitamin E is linked to better cognitive performance [32] there are still some studies that report some disadvantages [82,83,84,85,86,87,88,89]. For instance, the factors that may be involved with the intestinal absorption of vitamin E are not accurately available [82].…”
Section: Vitamin Ementioning
confidence: 99%
“…For instance, the pro-oxidative effects of high dose of vitamin E are linked with increased mortality [85] and incidents of heart failure [84,85]; α- and γ-tocopherol have pro-oxidant activity toward HDL (high density lipoprotein) [86,87] and α-tocopherols on type 2 diabetes patients, with respect to acute hyperglycaemia [88]. Clinical studies that involve vitamin E supplements also found that tocopherol could facilitate the formation of free radicals and this pro-oxidant effect may impact the increase in fatal myocardial infarctions [85,89].…”
Section: Vitamin Ementioning
confidence: 99%